Comparison of maternal and fetal morbidity between Patwardhan method of second stage lower segment caesarean section and conventional "push and pull" method - Hol, Kishorkumar; Trivedi, Sneha; Jaiswal, Shruti; Darawade, Sameer Popat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To compare Maternal and fetal morbidity between Patwardhan method of second stage LSCS and conventional "push and pull" method. Methods: A retrospective study of all LSCS performed in second stage of labour consisted of all cases delivered by Patwardhan method compared with cases delivered by Push method during 3 years from January 2016 to December 2018 in Smt. Kashibai Navale Medical College Pune, Maharashtra, India. Results: A total of 89 patients underwent second stage LSCS from January 2016 to December 2018. A total of 37 patients were delivered by Patwardhan’s method and 52 patients were delivered by Push method. Uterine incision extension was more in the push and pull method when compared to Patwardhan technique. Same was true for the traumatic PPH blood transfusion which was significantly high in push and pull method as compared. Neonatal morbidity was significantly less in Patwardhan’s method as compared to Push method. Conclusions: As the maternal and fetal complications are seen to be considerably less in Patwardhan’s method than the conventional Push method our study concludes that Patwardhan’s method for delivering baby in second stage LSCS confers greater advantage.